An introduction to quantum optics : photon and biphoton physics - Shih, Yanhua (Boca Raton : CRC Press, 2021)
"This text offers a complete revision for its introduction to the quantum theory of light, including notable developments as well as improvements in presentation of basic theory and concepts, with continued emphasis on experimental aspects. The author provides a thorough overview on basic methods of classical and quantum mechanical measurements"--
OCLC-licensed vendor bibliographic record.
Keywords: Quantum optics; SCIENCE / Quantum Theory; TECHNOLOGY / Lasers